Microwave ablation with hydrodissection used for the treatment of vascular malformations: effectiveness and safety study - Wang, Lu; Lu, Man; Zhuang, Min; Liang, Ying; Wang, Shi Shi; Li, Jia Mi (Frontiers in Oncology, 2024)
The aim of the study was to investigate the safety, effectiveness, and peripheral nerve protection in ultrasound-guided microwave ablation (US-guided-MWA) for vascular malformations (VMs) closely related to peripheral nerve.From August 2019 to February 2022, 31 patients with 39 VMs received US-guided-MWA. All lesions were confirmed to be closely related to the peripheral nerve by imaging evaluation. Hydrodissection was applied to protect surrounding normal tissue, including peripheral nerves. The patients were followed up at 1day, 2 days, 3 days, 1 week, 1 month, 3 months after operation. Measurements of lesion volume, volume reduction ratio (VRR), sensory and functional abnormalities of adjacent nerves, number of treatments, complication details, personal satisfaction, recurrence, and symptom improvement were recorded. Results: Among the 39 VMs, the maximum volume is 128.58ml, while the minimum volume is 0.99ml. After a mean follow-up of 13.06±4.83 months, the mean numerical rating scale (NRS) score decreased from 5.13±1.65 to 0.53±0.83 (P＜0.0001). The mean mass volume was reduced from 18.34±24.68 ml to 1.35±2.09 ml (P=0.0001). The VRR of all lesions was 92.06%. However, the mean number of treatments was only 1.64±0.87. All patients were satisfied with the technique, with a mean satisfaction score (SC) of 9.23±1.13. There were no motor function abnormalities of the related nerves. 10 patients felt numbness in the ablation area after ablation, and gradually recovered after 1 month. Conclusion: US-guided-MWA serves as a novel alternative approach for patients with VMs. Preoperative evaluation of the relationship between VMs and peripheral nerves combined with intraoperative hydrodissection is an effective and safe method to prevent nerve injury.Vascular malformations (VMs) are complex congenital lesions with various clinical manifestations that may affect patients' lives [1]. VMs include capillary malformations, venous malformations, lymphatic malformations, arteriovenous malformations, congenital arteriovenous malformations, and mixed malformations [2][3]. VMs can involve all parts of the body, including dermis, subcutaneous tissue, muscles, bones, and even internal organs. The ones that affect dermis,